Threads of Life: The Golden Age Midwife admdist Cloth, Tissue and Antique Deities of Fate - Grohsebner, Sabrina (Avisos de Viena, 2020)
In Golden Age Spain, childbirth assistance intertwined with ritualistic practices mediated by midwives. This study explores the symbolic significance of childbirth rituals, drawing parallels with ancient Roman and Greek deities of fate. The midwife, akin to the divine sisters of destiny, assumes a multifaceted role, shaping both physical and moral destinies. Symbolic associations between textile production and reproduction further enrich the analysis, revealing societal perceptions of female handcrafters and midwives. Through an examination of literary, artistic, and cultural artifacts, this research uncovers the intricate connections between fate, reproduction, and handicrafts in Golden Age society. It also suggests avenues for further exploration, including the representation of the umbilical cord, social attitudes towards different fabric productions, and etymological investigations into relevant terminology. Ultimately, this study illuminates the profound cultural and symbolic dimensions of childbirth assistance in Golden Age Spain.